A critical review of combined natural ventilation techniques in sustainable buildings. (May 2021) - Zhang, Haihua; Yang, Dong; Tam, Vivian W.Y.; Tao, Yao; Zhang, Guomin; Setunge, Sujeeva; Shi, Long
Abstract: Combination of natural ventilation approaches is a new trend for free space cooling/heating in buildings. A critical review was then undertaken to provide an overview of the combined technologies that hope to initialize new ideas and promote future endeavors. The advantages of the integrated natural ventilation systems can be summarized into several principles, including achieving beyond the existing performance by single system, maintaining indoor temperature stability, realizing heat energy recovery, overcoming the inadequacy of a single system, and providing a more comprehensive and useful energy-saving scheme. Most of the existing studies on combined systems are found based on thermal buoyancy, while only a small amount dealt with the combination of wind-driven and buoyancy-induce due to the complexity. Parametric studies in most previous studies focused on several major ones, so a systematic analysis is critically needed to address the performance of the overall combination to achieve stable and durable performance. A thoughtful investigation is also required to avert unpredictable delivery of air ﬂow, such as through the manipulation of external wind forces. The related research focuses should also be shifted following the trend of multi-storey buildings under the rapidly growing population. No guideline was found that arranges these natural ventilation systems in terms of performance and applicability for their practical selections and usages. Also, the thermal bridge breaking in cold winter and condensation in summer may compromise the natural ventilation performance and durability, and longevity of buildings. The studies on the coupling between different natural ventilation systems are still insufficient, requiring quite a bit of effort in future works. Highlights: Combined natural ventilation systems in single building were reviewed. Advantages of combined natural ventilation systems were summarized. Existing systems much reply on thermal buoyancy but not combined buoyancy and wind. Research focuses should be shifted following the trend of multi-storey buildings. Studies on coupling different natural ventilation systems are still insufficient.